I sing the body electric! : and other stories - Bradbury, Ray. 1920-2012 (Perennial, 2001)
A collection of twenty-eight classic Bradbury short stories and one poem, set in a variety of locales ranging from the verdant Irish countryside to the coldest reaches of outer space. His work is united by one common thread, a vivid and profound understanding of the vast seat of emotions that bring strength and mythic resonance to our frail species. A horrified mother may give birth to a strange blue pyramid. A man may take Abraham Lincoln out of the grave, and meet another who puts him back. An amazing electrical grandmother may come to live with a grieving family. An old parrot may have learned over long evenings to imitate the voice of Ernest Hemingway, and become the last link to the last link to the great man. A priest on Mars may confront his fondest dream to meet the Messiah. Each of these magnificent creations has something to tell us about our own humanity, and all of their fates await you in these classic Bradbury stories (and poem).